2002
DOI: 10.1057/iaor.2002.289
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility versus efficiency? A case study of model changeovers in the Toyota production system

Abstract: T his is a careful and insightful case study of how the Toyota Production System manages the paradox of efficiency and flexibility, which arises periodically in connection with model changeovers. The authors detail the functioning of four organizational mechanisms-metaroutines, partitioning, switching, and ambidexterity. However, of particular interest is the contextual reinforcing role of training and trust in administrative structures, procedures, and rules. AbstractThis article seeks to reconceptualize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
609
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(629 citation statements)
references
References 37 publications
(52 reference statements)
10
609
0
10
Order By: Relevance
“…Much organization theory argues that exploitation requires efficiency, that efficiency requires bureaucracy, that bureaucracy impedes flexibility, which is a prerequisite for exploration, and that organizations therefore confront a tradeoff between efficiency and flexibility (Adler & Borys, 1996;Adler, Goldoftas, & Levine, 1999). Such a relationship suggests that efficiency and flexibility may be viewed as two ends of a continuum, as illustrated in Figure 1.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Much organization theory argues that exploitation requires efficiency, that efficiency requires bureaucracy, that bureaucracy impedes flexibility, which is a prerequisite for exploration, and that organizations therefore confront a tradeoff between efficiency and flexibility (Adler & Borys, 1996;Adler, Goldoftas, & Levine, 1999). Such a relationship suggests that efficiency and flexibility may be viewed as two ends of a continuum, as illustrated in Figure 1.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…From an organizational point of view, efficiency requires a bureaucratic form of organization with high levels of standardization, formalization, and specialization. However, such bureaucratic features impede the fluid process of mutual adjustment required for the flexibility that is essential for strategic adaptability to environmental changes (Adler et al, 1999). Focusing on the other end of the efficiency-flexibility continuum, such a perspective emphasizes a firm's capability to respond to rapid changes and to quickly re-align with the environment (Sanchez, 1995).…”
Section: Efficientmentioning
confidence: 99%
“…The Olhager and West approach is interesting because it clearly demonstrates the tremendous amount of analysis and effort required to perform this translation of market demand into flexibility competences. Adler et al (1999) suggested that companies could reduce the trade-off through what they called ''ambidexterity'': investing in the ability of employees to be both flexible and efficient. Ambidexterity included tactics such as (a) metaroutines, or routinizing innovative tasks; (b) job enrichment through adding nonroutine tasks to the operator's work; (c) switching, or dividing employee time between tasks requiring efficiency and tasks requiring flexibility; and (d) partitioning, or creating subunits in the organization specialized in either routine or nonroutine tasks.…”
Section: Trading Off Between Efficiency and Flexibilitymentioning
confidence: 99%
“…Through ambidexterity, organizations avoid what Christensen (1997) described as 'the innovator's dilemma', where companies with the advantage of a new technology or approach fail as a consequence of pursuing it along with the forms of organizing that it demands. Strategic change subsequently becomes a constant process of shifting the trade-off between organizing forms that encourage either flexibility or efficiency (Adler et al, 1999). Discrete activities such as knowledge acquisition have to be combined with common activities providing effective organizational controls (Ilinitch et al, 1996).…”
Section: Proposition 2: Tension Between Forms Of Organizing Is a Sourmentioning
confidence: 99%